Incidencia de embarazos no planificados y su relación con inicio tardío de control prenatal en el Subcentro de Salud “Patria Nueva” en el último trimestre del año 2014. - Salazar Calva, Edgar Alexander (2015)
Unplanned pregnancy comes and settles in society when planning is technically possible with medical contraceptive technology, assuming a high rationalization and objectification of reproductive practice, separating sexual practice, so is objectified, measurable and independent of individual. The lack of pregnancy planning is one of the great problems of reproductive, sexual and social health in developed and developing countries. About half of all pregnancies are unplanned, and half of them end in induced abortion.